2020
DOI: 10.1128/mbio.00416-20
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Secondary Metabolite Biosynthetic Potential in Soil Varies with Phylum, Depth, and Vegetation Type

Abstract: Bacteria isolated from soils are major sources of specialized metabolites, including antibiotics and other compounds with clinical value that likely shape interactions among microbial community members and impact biogeochemical cycles. Yet, isolated lineages represent a small fraction of all soil bacterial diversity. It remains unclear how the production of specialized metabolites varies across the phylogenetic diversity of bacterial species in soils and whether the genetic potential for production of these me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
112
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 75 publications
(94 reference statements)
12
112
0
2
Order By: Relevance
“…From the twelve BGCs detected in Gemmatimonadetes, eight bacteriocins were detected suggesting this phylum may contain a greater biosynthetic capacity than previously thought (Figure 3). Similarly, a recent metagenomics soil study described bacteriocins being the prominent gene cluster detected in the genomes of Gemmatimonadetes (Sharrar et al, 2020). We report the prevalence of bacteriocin clusters in the genome of Gemmatimonadetes recovered from hypersaline microbial mats which appear to share similar biosynthetic capacities seen in the genomes of Gemmatimonadetes inhabiting soil environments.…”
Section: Detection Of Bgcs In Mags With Assigned Taxonomiessupporting
confidence: 63%
See 1 more Smart Citation
“…From the twelve BGCs detected in Gemmatimonadetes, eight bacteriocins were detected suggesting this phylum may contain a greater biosynthetic capacity than previously thought (Figure 3). Similarly, a recent metagenomics soil study described bacteriocins being the prominent gene cluster detected in the genomes of Gemmatimonadetes (Sharrar et al, 2020). We report the prevalence of bacteriocin clusters in the genome of Gemmatimonadetes recovered from hypersaline microbial mats which appear to share similar biosynthetic capacities seen in the genomes of Gemmatimonadetes inhabiting soil environments.…”
Section: Detection Of Bgcs In Mags With Assigned Taxonomiessupporting
confidence: 63%
“…A previous 16S rRNA survey of Shark Bay microbial mats revealed the surface layer being dominated and overrepresented by Alpha-, Gammaproteobacteria, Bacteroidetes, and Cyanobacteria (Wong et al, 2015). A recent study also found BGCs from Gammaproteobacteria were enriched in shallow sections of soil (Sharrar et al, 2020). Gammaproteobacteria and Cyanobacteria are known prolific secondary metabolite producers and Bacteroidetes have previously been reported to encode for a range of bacteriocins thus supporting the relatively high count of BGCs at the surface layer (Wang et al, 2014;Lopetuso et al, 2019;Reddy et al, 2020).…”
Section: Bgc Abundance Comparison In Different Microbial Mat Layersmentioning
confidence: 87%
“…Notable was the unexpected phylum-level diversity of CPR lineages in the concentrate metagenomes. Previously, a genome of TM7 (Saccharibacteria) was reported from the same soil, but sampled at less than 1x coverage from bulk soil (6), and Microgenomates and Parcubacteria have been genomically sampled twice at low abundance (12,16). To our knowledge, this is the first report of Pacearchaeota, Doudnabacteria and potentially a novel clade of Saccharibacteria in soil.…”
Section: Resultsmentioning
confidence: 86%
“…Actinobacteria continue to be the main source of clinically used antimicrobials (van Bergeijk et al ., 2020), but genome mining strategies are revealing the enormous genetic potential of alternative microbial taxa to discover novel antibiotics (Blin et al ., 2019; Sharrar et al ., 2020). This fact is exemplified in a recent study in Microbial Biotechnology where the combination of genome mining and phylogenetics of core polyketide synthase domains led to the discovery of an uncharacterized 35 kb biosynthetic gene cluster (BGC) in a fungal endophyte isolated from a traditional Chinese medicine plant.…”
mentioning
confidence: 99%
“…Despite AMR being a rising threat, recent efforts aimed at discovering and developing new antimicrobials in public and private sectors have not advanced significantly, with only 12 new antibiotics (or combinations) being approved in the last two decades (Kaufmann et al ., 2018). However, the rapid progress in the development of integrative platforms based on the combination of genomics, metagenomics, metabolomics and bioinformatics is facilitating the analysis of thousands of microorganisms in order to mine the antimicrobial biosynthetic potential of specific taxonomic groups and ecosystems (Sharrar et al ., 2020; van der Hooft et al ., 2020). In addition, recent algorithmic advancements in modelling neural networks have started to influence the paradigm of drug discovery (Stokes et al ., 2020).…”
mentioning
confidence: 99%